Evaluasi Kelembagaan Islam Konsep Evaluasi Kelembagaan Pendidikan Islam - Atik Likai Tanjua; Afindi Afindi; Hilman Nugraha; Desy Eka Citra Dewi (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Islamic education has a very important role in shaping the character and morals of individuals, as well as in developing quality human resources. Evaluation of Islamic educational institutions is one of the most crucial aspects in efforts to improve the quality of Islamic educational institutions as a whole. This article discusses the importance of institutional evaluation in Islamic education to measure the extent to which institutions can fulfill the vision, mission, and goals of Islamic education. Evaluation does not only cover academic aspects, but also character, morals, management, curriculum, human resources, facilities, and relations with the community. In addition, this article also identifies the basic principles in evaluating Islamic educational institutions, namely objectivity, transparency, and justice. This study uses a library research method by collecting and analyzing related literature, such as books, scientific journals, and academic articles. The results of the study indicate that evaluation of Islamic educational institutions functions as a tool for continuous improvement, supports accountability, and adapts the curriculum and learning methods to the needs of the times. In addition, the role of leaders in the evaluation process is vital to ensure the successful implementation of the evaluation. It is hoped that this article can contribute to the development of an effective and efficient institutional evaluation system in Islamic education.